Analisis Nilai Karakter Profil Pelajar Pancasila dalam Buku Cerita Tanah Papua untuk Pembelajaran Sekolah Dasar - Sabilla Rani Nur Ananta; Muhammad Sobri; Heri Setiawan (Mataram University, 2026)
This study aims to describe and analyze the Pancasila student profile character values found in the storybook “Dari Tanah Papua”. This is a qualitative descriptive study using content analysis as the data analysis method. The object of this study is the storybook “Dari Tanah Papua” by Muhammad Jaruki. Data collection was conducted through observation and documentation. Research instruments included an analysis sheet to identify character values in the book. Data were analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results show that there are 24 data points contained in the storybook “Dari Tanah Papua” that represent the six dimensions of the Pancasila Student Profile. The results indicate that the storybook “Dari Tanah Papua” contains the values of the Pancasila Student Profile, comprising 7 data points in the dimension of “Faith and Piety toward God the Almighty,” 6 data points in the dimension of “Cooperation,” 4 data points in the dimension of “Independence,” 2 data points in the dimension of “Critical Thinking,” 1 data point in the dimension of “Creativity,” and 4 data points in the dimension of “Global Diversity.” Based on the research results, it can be concluded that the storybook “Dari Tanah Papua” contains the values of the Pancasila Student Profile across six dimensions, making it suitable for use as teaching material to support the character development of students.